THE IMPORTANCE OF PUBLIC TRUST IN GOVERNMENT POLICIES IN EFFORTS TO ACCELERATE THE MANAGEMENT OF THE COVID 19 PLAGUE - Mahyuni Hidayat; Bambang Adi Wijaya; Bayu Lintang Samudro; Muzahid Akbar Hayat (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
Corona Virus Disease 2019 (Covid-19) is a pandemic that is being felt by almost all countries, including Indonesia. Apart from having an impact on the safety of people's lives, it also has an impact on the political and economic aspects. There have been many efforts and policies taken by the central and regional governments to date, but it is still felt that they have not given the public hope when this pandemic will end soon. This has the potential to harm public trust (Trust Public) in the performance of the government to handle the covid-19 outbreak. The purpose of this paper is to describe the alternatives that the government should try to do to increase public trust.